قول الصحابي وأثره في فقه المعاملات المالية - عبد القادر, يوسفات; نفسي, عبد القادر (جامعة الوادي university of eloued, 2023)
"هاته الدراسة الموسومة ب: قول الصحابي وأثره في فقه المعاملات المالية, كان الإشكال الرئيسي فيها هو: ما مدى حجية قول الصحابي؟ وما أثره في فقه المعاملات المالية؟ وللإجابة على هذا التساؤل انتهجنا خطة كانت كالآتي: المبحث الأول بعنوان مفهوم قول الصحابي، المبحث الثاني وفيه منهج الأصوليين في حجية قول الصحابي، والمبحث الثالث بعنوان أثر قول الصحابي في فقه المعاملات المالية، وفي الأخير خاتمة ذكرنا فيها أهم نتائج البحث: هو أن قول الصحابي حجة لا يسع المجتهدين إهماله أو تركه، كما أوصينا بضرورة إشراك المجامع العلمية المعاصرة قول الصحابي في بناء فتاواها وأحكامها المعاصرة. ""This study, titled: The Companion’s Saying and its Impact on the Jurisprudence of Financial Transactions, the main problem in it was: How authoritative is the Companion’s statement? What is its impact on the jurisprudence of financial transactions? To answer this question, we adopted a plan that was as follows: the first section is entitled The Concept of the Companion’s Saying, the second section contains the fundamentalists’ approach to the validity of the Companion’s statement, the third section is entitled The Impact of the Companion’s Saying on the Jurisprudence of Financial Transactions, and finally a conclusion in which we mentioned the most important results of the research: it is that the Companion’s statement An argument that scholars cannot afford to neglect or abandon, just as we have recommended the necessity of contemporary scholarly academies including the words of the Companions in constructing their contemporary fatwas and rulings. "
مذكرة
Keywords: قول الصحابي، فقه، معاملات مالية.; Keywords: the saying of the companion, jurisprudence, financial transactions.